A NEW SPECIES OF COPEPOD Caligus polynemi N. SP. FROM POLYNEMID FISHES OF VISAKHAPATNAM COAST, BAY OF BENGAL, ANDHRA PRADESH, INDIA (Applied Biological Research, 2023)
Caligids are one of the most frequently occurring copepod parasites of  marine and brackish water fishes, which cause a great havoc to the mariculture. There isahugebiodiversityof marine fishes andtheirparasites  in the Bay of Bengal. The present study was aimed to unravel the copepod  parasite diversity in marine thread fin fishes of Visakhapatnam coast,  Andhra Pradesh (India). A new species of Caligus Muller, 1785 was  obtained from the gills of 77 Polydactylus plebeius (Broussonet) and 55  Leptomelanosoma indicum (Shaw) of Visakhapatnam coast, India, fixed in  10% formalin and cleared ia few drops of lactic acid for 12-24 h before  identification. The species was characterized by having urn-shaped genital segment, large lunules, indistinctly two-segmented abdomen, converging  tines of sternal fork, presence of three rows of teeth on the middle segment  of endopod of 2nd leg, three segmented 4th leg and absence of ventral setae  on distal segment of 1st leg. Based on above differences in vital diagnostic  features and their occurrence in polynemid fishes, they are regarded as  new species of Caligus and named as Caligus polynemi n. sp. Further  monitoring surveys may enable sustainable marine fish farming by  exploring unknown species from different geographical locations and  develop various pest management anconservation strategies against them  to safeguard marine life.
Keywords: Caligus polynemi; Leptomelanosoma indicum; Polydactylus plebeius; Visakhapatnam coast